1991
DOI: 10.1111/j.1745-6592.1991.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Appendix IX Organic Constituents in Disposal Site Ground Water

Abstract: Monitoring data from 479 disposal site investigations were used to provide an initial estimate of the occurrence and distribution of 208 Appendix IX organic constituents in ground water. The most prevalent class of contaminants were the volatile organic compounds, which accounted for 84 percent of all the detectable events in the composite data set involving Appendix IX organic constituents. The abundance of the remaining subsets of Appendix IX organic constituents decreased in the following order: base/neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…These authors found that ethylbenzene was detected at ≈25% of the waste water effluents (receiving secondary treatment) and only 3% of the groundwater sampled in the vicinity of sanitary landfill sites. Groundwater monitoring at 479 hazardous waste disposal sites indicated that ethylbenzene, like the other 9 VOCs monitored, was detected at more than 100 of the 479 sites tested (Plumb 1991). Ethylbenzene was also one of the VOCs detected in groundwater samples from hazardous waste sites in all 10 EPA regions.…”
Section: Watermentioning
confidence: 97%
“…These authors found that ethylbenzene was detected at ≈25% of the waste water effluents (receiving secondary treatment) and only 3% of the groundwater sampled in the vicinity of sanitary landfill sites. Groundwater monitoring at 479 hazardous waste disposal sites indicated that ethylbenzene, like the other 9 VOCs monitored, was detected at more than 100 of the 479 sites tested (Plumb 1991). Ethylbenzene was also one of the VOCs detected in groundwater samples from hazardous waste sites in all 10 EPA regions.…”
Section: Watermentioning
confidence: 97%
“…Dichloroethylene includes three isomers: 1,1-dichloroethylene, cis-l,2-dichloroethylene, and trans-l,2-dichloroethylene. Preparations containing PCE and TCE have often been used as industrial solvents and degreasers and, along with petroleum products, together represent the most common organic contaminants found in groundwater and soil (Jiricek et al, 2007;Plumb, 1991). Currently, environmental contam ination by these substances is mainly a consequence of old ecological loads from old industrial manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…He suggested that monitoring for VOCs be used as an early warning system for excursions to indicate the need for more extensive laboratory analysis for organics, and that statistical considerations show that this will work correctly more than 90% of the time. The top 18 VOCs of interest are listed in Table 1 (Plumb 1991). A similar, but not identical, list was developed for sites in Germany (Kerndorff et al 1992).…”
Section: Introduction Halogenated Volatile Organic Compoundsmentioning
confidence: 99%